PREVALENCE OF ASTHMA-LIKE SYMPTOMS AND DIAGNOSED ASTHMA IN THE POPULATION OF ADOLESCENTS - L.S. Namazova-Baranova; L.M. Ogorodova; A.Yu. Tomilova; I.A. Deev; A.A. Alekseeva; E.A. Vishneva; I.A. Gromov; E.A. Evdokimova; E.M. Kamaltynova; I.L. Kolomeets; R.M. Torshkhoeva (Union of pediatricians of Russia, 2009)
Over the recent years, standardised epidemiological studies of asthma and asthma'like symptoms in the population of children have been conducted. ISAAC (International Study of Asthma and Allergy in Childhood) questionnaire has been predominantly used as a tool to assess the prevalence of clinical implications and diagnosed conditions in children. However, this technique has limitations in terms of subject age (children aged 6-7 and 13-14). We have conducted a study on the prevalence of Asthma and allergy in adolescents (children aged 15-17) using the standardised GA2LEN (Global Allergy and Asthma European Network) questionnaire in two Russian cities from central region and Siberia (Moscow and Tomsk). It has been found that the prevalence of asthma'like symptoms in adolescents was three times the level of clinically diagnosed asthma, which accounted for no more than 7%, with this indicator having no variance depending on the region of residence.Key words: asthma, GA2LEN, prevalence, epidemiology, adolescents.